Classical and novel properties of Holliday junction resolvase SynRuvC from Synechocystis sp. PCC6803 - Gu, Yanchao; Yang, Yantao; Kou, Chunhua; Peng, Ying; Yang, Wenguang; Zhang, Jiayu; Jin, Han; Han, Xiaoru; Wang, Yao; Shen, Xihui (Frontiers in Microbiology, 2024)
Cyanobacteria, which have a photoautotrophic lifestyle, are threatened by ultraviolet solar rays and the reactive oxygen species generated during photosynthesis. They can adapt to environmental conditions primarily because of their DNA damage response and repair mechanisms, notably an efficient homologous recombination repair system. However, research on double-strand break (DSB) repair pathways, including the Holliday junction (HJ) resolution process, in Synechocystis sp. PCC6803 is limited. Here, we report that SynRuvC from cyanobacteria Synechocystis sp. PCC6803 has classical HJ resolution activity. We investigated the structural specificity, sequence preference, and biochemical properties of SynRuvC. SynRuvC strongly preferred Mn2+ as a cofactor, and its cleavage site predominantly resides within the 5’-TG↓(G/A)-3’ sequence. Interestingly, novel flap endonuclease and replication fork intermediate cleavage activities of SynRuvC were also determined, which distinguish it from other reported RuvCs. To explore the effect of SynRuvC on cell viability, we constructed a knockdown mutant and an overexpression strain of Synechocystis sp. PCC6803 (synruvCKD and synruvCOE) and assessed their survival under a variety of conditions. Knockdown of synruvC increased the sensitivity of cells to MMS, HU, and H2O2. The findings suggest that a novel RuvC family HJ resolvase SynRuvC is important in a variety of DNA repair processes and stress resistance in Synechocystis sp. PCC6803.